2023
DOI: 10.3390/ijpb14030063
|View full text |Cite
|
Sign up to set email alerts
|

The Antioxidant and Antimicrobial Activities of Two Sun-Dried Fig Varieties (Ficus carica L.) Produced in Eastern Morocco and the Investigation of Pomological, Colorimetric, and Phytochemical Characteristics for Improved Valorization

Aziz Tikent,
Salah Laaraj,
Ahmed Marhri
et al.

Abstract: The eastern region of Morocco is renowned for the production of two varieties of figs, Ghoudane (GD) and Chetoui (CH), which are characterized by their high productivity and quality. To ensure a profitable selling price, producers often dry these figs, a process that not only increases their storage capability but also enhances their nutritional and health benefits. The aim of this study was to investigate the composition and potential health benefits of dried GD and CH figs. The findings of this study reveal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…In previous studies, the trunks, branches, and leaves of the fig tree were reported to have a variety of biological properties, including anticancer, antibacterial, antioxidant, and anti-inflammatory properties [17]. Two varieties of dried figs exhibited potential as natural sources of antioxidant and antimicrobial compounds, indicating significant correlations between phytochemical content and both antioxidant and antimicrobial activities [18]. Fig extract (an edible fruit) was utilized as both a capping and reducing agent to synthesize calcium oxide nanoparticles (CaONPs), suggesting the potential therapeutic value of these nanoparticles as antibacterial and antibiofilm agents in medications [19].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, the trunks, branches, and leaves of the fig tree were reported to have a variety of biological properties, including anticancer, antibacterial, antioxidant, and anti-inflammatory properties [17]. Two varieties of dried figs exhibited potential as natural sources of antioxidant and antimicrobial compounds, indicating significant correlations between phytochemical content and both antioxidant and antimicrobial activities [18]. Fig extract (an edible fruit) was utilized as both a capping and reducing agent to synthesize calcium oxide nanoparticles (CaONPs), suggesting the potential therapeutic value of these nanoparticles as antibacterial and antibiofilm agents in medications [19].…”
Section: Introductionmentioning
confidence: 99%